Iron-based nanoparticles for MR imaging-guided ferroptosis in combination with photodynamic therapy to enhance cancer treatment. Issue 9 (24th February 2021) - Chen, Qifang; Ma, Xianbin; Xie, Li; Chen, Wenjie; Xu, Zhigang; Song, Erqun; Zhu, Xiaokang; Song, Yang
Abstract : MR imaging-guided a synergistic ferroptosis-photodynamic therapy strategy can enhance antitumor effects by accumulating intracellular ROS through the utilization of iron-based nanoparticles. Abstract : Ferroptosis therapy, which applies ferroptotic inducers to produce lethal lipid peroxidation and induce the death of tumor cells, is regarded as a promising therapeutic strategy for cancer treatment. However, there is still a challenge regarding how to increase reactive oxygen species (ROS) accumulation in the tumor microenvironment (TME) to enhance antitumor efficacy. Herein, we designed a nanosystem coated with the FDA approved poly(lactic- co -glycolic acid) (PLGA) containing ferrous ferric oxide (Fe3 O4 ) and chlorin E6 (Ce6) for synergistic ferroptosis-photodynamic anticancer therapy. The Fe3 O4 -PLGA-Ce6 nanosystem can dissociate in the acidic TME to release ferrous/ferric ions and Ce6. Then, the Fenton reaction between the released ferrous/ferric ions and intracellular excess hydrogen peroxide can occur to produce hydroxyl radicals (˙OH) and induce tumor cell ferroptosis. The released Ce6 can increase the generation and accumulation of ROS under laser irradiation to offer photodynamic therapy, which can boost ferroptosis in 4T1 cells. Moreover, magnetic monodisperse Fe3 O4 loading provides excellent T 2 -weighted magnetic resonance imaging (MRI) properties. The Fe3 O4 -PLGA-Ce6 nanosystem possesses MRI ability and highly efficient tumor suppression with high biocompatibility in vivo due to the synergism of photodynamic and ferroptosis antitumor therapies.